The Effect of Changes in Communist Ideology after 1953 on repressive Policies and KGB Operations - Burinskaitė, Kristina (Genocidas ir rezistencija, 2013)
Communist ideology and its changes after 1953 were an important indicator of internal developments in the Soviet Union and its repressive policies. The ideology legitimated persecution of dissenters and established the use of specific methods against them. The new ideological concepts concealed reprisals against resistance fighters, because anti-Soviet activities were criminalised or portrayed as acts of mentally ill people. Perhaps the most important concept of the Communist ideology having an effect on the repressive policies of the Soviet Union was the so-called Western ideological sabotage, which was considered to be the source of all manifestations of anti- Soviet activity. All contacts with the West were therefore perceived as threatening to the socialist system and became a special focus for the KGB. Even the improved relations with the West did not prevent the continued offensive of propaganda, intelligence work, and disinformation against the West. The concept of “dictatorship of the proletariat” was replaced with the concept of the “all-people’s state”, which was concealed Russification leading to the destruction of national aspirations.